Trends in ringing numbers of forty bird species at Stora Fjäderägg Bird Observatory, north-eastern Sweden, 1985–2014 - Edenius, Lars; Alseryd, Niklas Lindberg; Wulff, Sören (Ornis Svecica, 2015)
Very few data series are available on the long-term development of the bird fauna in northern Sweden. This kind of data is of great interest as there are recent signs that bird populations in northern Sweden are developing less favourable than in southern Sweden. We present trends in annual capture rates of 40 frequently ringed species at Stora Fjäderägg Bird Observatory, NE Sweden, autumns 1985–2014. Significant positive and negative trends were found in ten and eight species, respectively. Great tit, Chaffinch and Long-tailed Tit showed the strongest increases, whereas Northern Wheatear, Willow Tit and Bluethroat decreased the most. There was a significant negative trend in capture index for short-distance migrants and a positive trend for irruptive species/partial migrants. For many species, particularly those that were decreasing, the trends at Stora Fjäderägg are similar to population trends seen in Swedish and Finnish breeding bird surveys. For these species the trends at Stora Fjäderägg could be indicative of long-term population changes.